2015
DOI: 10.15640/jaes.v4n1a29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Pond Effluent and Inorganic Fertilizer on Amaranthus Yield and Soil Chemical Properties in Asaba, Delta State, Nigeria

Abstract: An experiment was conducted at the Department of Agronomy Experimental Farm, Delta State University, Asaba Campus in 2011 early and late cropping seasons to evaluate the effects of fish pond effluent and inorganic fertilizer on amranthus performance. The study had five levels of fish pond effluent (0, 5, 10, 15 and 20t/ha) and five levels of inorganic fertilizer (0, 100, 150, 200 and 250 kg/ha), laid out in randomized complete block design with four replications. Number of leaves, leaf area, plant girth, leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Application of farmyard manure along + NPK (N 3 ) had significantly influenced the vegetative growth of fodder cowpea in terms of number of leaves per plant (20.73), leaf Assessment of Leaf Area Index and its Relationship with Growth and Yield of Fodder Cowpea as Influenced by Sources of.... Assessment of Leaf Area Index and its Relationship with Growth and Yield of Fodder Cowpea as Influenced by Sources of.... length (25.13 cm) and leaf width (20.73) followed by application of NPK alone (N 4 ). Domestic sewage water can be used as a fertilizer or soil amendment which in turn has the ability to improve growth rate of crops (Ojobor and Tobih 2015). The present study had the similar findings and may corroborated to the fact that the availability of nutrients in domestic sewage water would have enhanced the nutrients available in the soil and hence the availability of nutrients to the plants to improve growth parameters.…”
Section: Vegetative Growth Of Fodder Cowpeasupporting
confidence: 83%
“…Application of farmyard manure along + NPK (N 3 ) had significantly influenced the vegetative growth of fodder cowpea in terms of number of leaves per plant (20.73), leaf Assessment of Leaf Area Index and its Relationship with Growth and Yield of Fodder Cowpea as Influenced by Sources of.... Assessment of Leaf Area Index and its Relationship with Growth and Yield of Fodder Cowpea as Influenced by Sources of.... length (25.13 cm) and leaf width (20.73) followed by application of NPK alone (N 4 ). Domestic sewage water can be used as a fertilizer or soil amendment which in turn has the ability to improve growth rate of crops (Ojobor and Tobih 2015). The present study had the similar findings and may corroborated to the fact that the availability of nutrients in domestic sewage water would have enhanced the nutrients available in the soil and hence the availability of nutrients to the plants to improve growth parameters.…”
Section: Vegetative Growth Of Fodder Cowpeasupporting
confidence: 83%
“…Domestic wastewater was traditionally used as a fertilizer in agriculture or as soil conditioner, and pond effluent has been used to improve the growth rate and quality of crops (Wood et al 2001;Naddafi et al 2005;Ojobor and Tobih 2015). This present study investigated the effects of artificial pond wastewater (APWW)-treated soil on the growth and biochemical indices of cowpea seedlings.…”
Section: Resultsmentioning
confidence: 98%
“…The report of FAO (2014) has also shown that the residue that settles in fish ponds as silt are rich in nutrient and, therefore, wastewater from fish pond is a useful organic fertilizer for crop cultivation. In a like manner, fish pond effluent had been applied in the cultivation of crops such as French beans (Meso et al 2007), amaranthus (Ojobor and Tobih 2015), pineapple and garden egg . Literature search indicates dearth of information in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment reported here set out to test the efficacy of aquaculture effluent as a fertiliser in a Martian simulant and a Martian analogue. The viability of freshwater aquaculture effluent as fertiliser has been demonstrated for a wide variety of food crops grown in terrestrial soils, including wheat (Al-Jaloud et al,, 1993), barley (Hussain and Al-Jaloud, 1998;Stevenson et al, 2010), maize (Abdul-Rahman et al, 2011;Osaigbovo et al, 2010), sorghum (Kolozsvári et al, 2022), soybean (Abdelraouf, 2017), amaranth (Ojobor and Tobih, 2015), potato (Abdelraouf, 2017), common bean (Meso et al, 2014), tomato (Castro et al, 2006;Pattillo et al, 2020), pepper (Omotade et al, 2019;Palada et al, 2019), chicory (Lenz et al, 2021a), cabbage (Elsbaay and Darwesh, 2022), lettuce (Lenz et al, 2021b), radish (Abdul-Rahman et al, 2011, cucumber (Ndubuisi, 2019), onion (Abdelraouf et al, 2016;Abdelraouf, 2017), basil (Omeir et al, 2020), marjoram (Kimera et al, 2021a) and oregano (Kimera et al, 2021b). This paper discusses a small pilot/proof of concept study, to ascertain whether aquaponic fish effluent could be used in sterile regoliths to produce vegetables.…”
mentioning
confidence: 99%